Intrinsic Coagulation Pathway, History of Headache, and Risk of Ischemic Stroke. Issue 8 (August 2019) - van Os, Hendrikus J.A.; Wermer, Marieke J. H.; Rosendaal, Frits R.; Govers-Riemslag, José W.; Algra, Ale; Siegerink, Bob S.
Abstract : Background and Purpose—: Hypercoagulable states in migraine patients may play a role in the pathophysiology underlying the association between migraine and ischemic stroke. This study aims to provide more insight into the potential association of headache, ischemic stroke, and the intrinsic coagulation pathway. Methods—: We included patients from the RATIO study (Risk of Arterial Thrombosis in Relation to Oral Contraceptives), a Dutch population-based case-control study including young women (age <50) with ischemic stroke and healthy controls. We defined a headache group based on a questionnaire on headache history. Intrinsic coagulation proteins were measured through both antigen levels (FXII, FXI, prekallikrein, HK [high molecular weight kininogen]) and protein activation, determined by measuring activated protein complex with C1esterase-inhibitor (FXIIa-C1-INH, FXIa-C1-INH, Kallikrein-C1-INH) or antitrypsin-inhibitor (FXIa-AT-INH). We calculated adjusted odds ratios and performed an interaction analysis assessing the increase in stroke risk associated with high levels of intrinsic coagulation and history of headache. Results—: We included 113 ischemic stroke cases and 598 healthy controls. In total, 134 (19%) patients had a history of headache, of whom 38 were cases and 96 controls. The combination of headache and high intrinsic coagulation protein levels (all but FXII antigen level and both FXIa-inhibitors) was associated with an increase in ischemic stroke risk higher than was expected based on their individual effects (adjusted odds ratio FXI antigen level alone: 1.7, 95% CI, 1.0–2.9; adjusted odds ratio headache alone: 2.0, 95% CI, 1.1−3.7; combination: 5.2, 95% CI, 2.3−11.6) Conclusions—: Headache and high intrinsic coagulation protein levels may biologically interact, increasing risk for ischemic stroke. Abstract : Supplemental Digital Content is available in the text.